(untitled) (Journal of Nepal Geological Society, 1982)
The paper presents the results of geophysical surveys carried out using induced polarization (IP) time-domain method with dipole-dipole configuration for the investigation of sulphide ore bodies in Kurule, Wapsa and Kalitar copper prospects of Nepal. IP anomalies were observed in all the prospects which were subsequently checked by drilling. Sulphide mineralization in disseminated forms and in lenses were found. The IP time-domain dipole-dipole method was found successful in the detection of disseminated sulphide mineralization even if its grade was very low.